The Student Intersction In Learning English - Nazry Nasyifa; Aisyah Hafizha; Fadiah Nur Amalia; Zahira Shofa; Nadiya Fitria; Didik Santoso (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
Through the use of instructional games, this study investigates the function of student engagement in the acquisition of the English language. This study uses a combination of in-depth interviews, thematic analysis, and direct observation along with qualitative research methodologies to investigate the dynamics of student interaction in a game-based learning environment. The findings demonstrated that the usage of games greatly enhanced language proficiency, student engagement, and communication abilities. During the game sessions, there was a 40% rise in the use of new vocabulary and a 60% increase in English verbal contact. Furthermore, 80% of groups demonstrated greater levels of cooperation, and 75% of students actively participated in class. The use of mother tongue has decreased by 30% as well. This study shows that game-based learning has significant potential to enhance students' linguistic competency and collaborative skills in learning English, despite obstacles like uneven participation and other distractions. The significance of choosing games that are suitable, providing scaffolding, managing the classroom well, and incorporating formative assessment strategies are all practical implications for educators.